PERANCANGAN APLIKASI KAMUS DIGITAL BAHASA LAWANGAN – BAHASA INDONESIA - Ariesta Lestari; Nahumi Nugrahaningsih; Dwiani Septiana (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2023)
Local language is a representation of cultural identity. Apart of being used as communication tools, local language also contains valuable values and local language. Central Kalimantan has a lot of undocumented local language, etiher conventially, let alone digitally. The purposes of this research is to provide a digital vocabulaty of Dayak Lawangan in Central Kalimantan. The stages in Rapid Application Develoment (RAD) method was adopted to build the application. The method was chosen because it is suitable for the lack of development time but it still can provide a precise and complies with the stages of making an application. With this applicatioin, it is hoped that the existence of local language of Dayak Lawangan community can be well documented in order to maintain the diversity.